Pelatihan sistem akuaponik berbasis sumbu menggunakan limbah di Desa Simbang Wetan, Kabupaten Pekalongan - Pujiono, Imam Prayogo; Ismanto, Kuat; Rohmah, Syifa; Prayogi, Arditya; Syukron, Akhmad Aufa; Suharyadi, Suharyadi (Jurnal Tarreang: Tren Pengabdian Masyarakat Agrokompleks, 2025)
Simbang Wetan Village faces a dual challenge: the accumulation of unmanaged flannel waste from the local convection industry and the need to enhance household-level food security. This community service activity aimed to transfer appropriate technology in the form of an innovative aquaponics wick system that utilizes flannel waste as a key functional component. The method employed a participatory learning approach, combining presentations, hands-on practice, and discussions. This activity was conducted on September 8, 2025, at the Simbang Wetan Village Hall, involving 24 residents. The program's success was measured quantitatively using pre-test and post-test instruments. Data analysis revealed a highly significant improvement in understanding and skills. Specific knowledge regarding the function of flannel fabric as an aquaponics wick surged dramatically from 8.3% in the pre-test to 100% in the post-test. Similarly, practical understanding of assembling the system from recycled materials increased from 4.1% to 87.5%. These results indicate that the workshop was highly effective in transferring knowledge and shifting the community's paradigm towards waste management. The broader adoption of this technology at the household level, along with continuous mentoring, is recommended to ensure program sustainability.